The Role of Service Quality, Trust, and Security in Enhancing Customer Satisfaction in Digital Wallet DANA Applications - Vivin Hanitha; Angreni, Tri; Hendra; Ruruh Wuryani (RUBINSTEIN, 2026)
Financial technology has encouraged the widespread adoption of digital wallet applications as practical and efficient tools for conducting payment transactions. This study aims to analyze the influence of service quality, trust, and security on customer satisfaction among users of the DANA digital wallet application in Tangerang City. This research employed a quantitative approach using survey questionnaires distributed to DANA 100 users with purposive sampling techniques. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among the variables. The results indicate that service quality has a positive and significant effect on customer satisfaction. Meanwhile, trust and security demonstrate positive but statistically insignificant effects on customer satisfaction. This finding implies that although users perceive trust and security as important factors, these variables do not strongly determine satisfaction levels in this study. Furthermore, the R-Square value of 0.739 indicates that service quality, trust, and security collectively explain 73.9% of the variance in customer satisfaction, the other 26.1% is influenced by other factors.